Cloud ERP Dialectics and Accounting Conflicts: Trust Mechanisms in Cross Functional Collaboration - Adi Wibowo, Wahyu; Adi cahyanto, Kurnia (Inovasi Analisis Data, 2025)
Purpose: We examine the impact of competing institutional logics imprinted in Cloud-ERP systems Economisation, Accessibility and Transparency on cross-functional collaboration (CFC) behaviour between accounting and IS (AI) professionals and the moderating role of trust-based collaboration mechanisms.Method: A quantitative method was used, with a structured questionnaire (n = 210) from ERP-experienced respondents in Indonesian firms. Multiple and moderated regression in SPSS were employed for the analysis of the data to test direct and interaction effectsFindings: Economisation Logic had a negative effect on Collaboration Effectiveness, while Accessibility and Transparency Logics had a strong positive effect. Dialectical tensions among these logics lowered the quality of collaboration when unregulated. Trust-Based Collaborative Mechanism (TBCM), positively moderated these relationships native scored positively but significantly higher, improving cooperation and reducing conflict.Novelty: This work is the first to provide an integrated model integrating dialectical institutional logics and trust-based mechanisms in the Cloud-ERP sector not much of such work done before particularly in the emerging economics.Implications: The results offer worldwide lessons for ERP system managers, implementing consultants, and policy makers in how to reconcile competing logics of departments and develop trust mechanisms for bolstering ERP project success and cross-functional alignment in enterprise digital transformation.